E-Learning Experiences of Higher Education Institutions in The Republic of Serbia During Covid-19, Content Analysis and Case Study ITS Belgrade - Goran RADIĆ; Bojan S. RISTIĆ; Svetlana ANĐELIĆ; Valentin KULETO; Milena ILIĆ (Communications of International Proceedings, 2020)
The hasty entering into the online learning system caused by the Covid-19 pandemic has brought certain benefits to students, governments and educational institutions, while on the other hand it has demonstrated certain shortcomings. Neither all students have fast internet, functional hardware, or the required level of information and communication technology skills nor all educators have digital competence. Apart from students, educators were even more expected to know information and communication technologies, and those who do not have required knowledge did not have enough time to get to know and learn. The transition to online learning has been a big challenge for governments, education systems and schools, so it is important to share knowledge and experience to learn important lessons because due to the Covid-19 pandemic the online learning expectations are high. The online learning system is considered to be the basis for creating a hybrid form of learning and a catalyst for a change of formal education. The paper is based on the available information using the content analysis method and observation with participation describes the experiences of higher education institutions in the Republic of Serbia with e-learning concepts which those institutions used for teaching students as a response to Covid-19 epidemiological measures, the prohibition of assembly and a state of emergency that has been declared throughout the country. Paper presents a case study as an example of good practice E-learning Experience of Information Technology School – ITS which uses a proactive approach and nurtures the quality culture. ITS is the first accredited private higher education institution in the sphere of information technology in Serbia. In addition to offering quality in the sense of excellent conditions for studying, state-of-the-art equipment, and highly trained personnel, ITS prepares students for a practical professional in IT while they are still in school. In the ITS curriculum, the school has included global computer science education standards, implemented top-quality programs and it`s incorporated founders’ experience after years of working in IT education.
Keywords: E-learning; online learning; Covid-19; Information and Communications Technology; Smart University; digital competency